Tuning perovskite oxides by strain: Electronic structure, properties, and functions in (electro)catalysis and ferroelectricity. (December 2019) - Hwang, Jonathan; Feng, Zhenxing; Charles, Nenian; Wang, Xiao Renshaw; Lee, Dongkyu; Stoerzinger, Kelsey A.; Muy, Sokseiha; Rao, Reshma R.; Lee, Dongwook; Jacobs, Ryan; Morgan, Dane; Shao-Horn, Yang
Graphical abstract: Abstract: Complex oxides, such as ABO3 perovskites, are an important class of functional materials that exhibit a wide range of physical, chemical, and electrochemical properties, including high oxygen electrocatalytic activity, tunable electronic/ionic conductivity, and ferroelectricity. When complex oxides are engineered as thin films, their chemical and physical properties can be modified to be markedly different from their bulk form, providing additional degrees of freedom in materials design. In this review, we survey the landscape of strain-induced design of complex oxides in the context of oxygen electrocatalysis and ferroelectricity. First, we identify the role of strain in influencing oxide electronic properties, driven by the combination of modification of BO bond length and octahedral distortion in perovskites. We describe electronic structure parameters, such as the O 2 p -band center, that quantitatively capture these electronic changes, highlighting the broad influence of the O 2 p -band center on surface reactivity (oxygen adsorption and dissociation energy) and bulk defect energetics (oxygen vacancy formation and migration energy). Motivated by the promise of the influence of strain on material properties relevant for oxygen electrocatalysis and ferroelectricity, we describe the advances in state-of-the-art thin-film fabrication and characterization that have enabled a high degree of experimental control in realizing strain effects in oxide thin-film systems. In oxygen electrocatalysis, leveraging strain has not only resulted in activity enhancements relative to bulk unstrained material systems but also revealed mechanistic influences of oxide phenomena, such as bulk defect chemistry and transfer kinetics, on electrochemical processes. Similarly for ferroelectric properties, strain engineering can both enhance polarization in known ferroelectrics and induce ferroelectricity in material systems that would be otherwise non-ferroelectric in bulk. Based on understanding of a diverse range of perovskite functionalities, we offer perspectives on how further coupling of strain, oxygen electrocatalysis, and ferroelectricity opens up pathways toward the emergence of novel device design features with dynamic control of increasing complex chemical and high-performance electronic processes.